Pain in People with Multiple Sclerosis: Associations with Modifiable Lifestyle Factors, Fatigue, Depression, Anxiety, and Mental Health Quality of Life - Marck, Claudia H.; De Livera, Alysha M.; Weiland, Tracey J.; Jelinek, Pia L.; Neate, Sandra L.; Brown, Chelsea R.; Taylor, Keryn L.; Khan, Fary; Jelinek, George A. (Frontiers in Neurology, 2017)
Background: People with multiple sclerosis (MS) often experience pain, which can interfere with mobility, employment and quality of life (QOL). Methods: This cross-sectional study explored associations between pain, demographic, disease, and modifiable lifestyle factors in an international sample of people with MS recruited online. Results: Substantial pain, of moderate/severe intensity and interfering at least moderately with work/household or enjoyment of life in the past four weeks, was reported by 682/2362 (28.9%). Substantial pain was associated with fatigue (Odds Ratio (OR): 6.7, 95% Confidence Interval (CI): 4.9,9.3), depression (OR:4.0, 95% CI:3.2,5.1), anxiety (OR:2.4, 95% CI:1.9,2.9) and lower mental health QOL (Mean Difference (MD): -14.7, 95% CI:-16.6,-12.8). Regression analyses showed that smoking (OR: 2.0, 95% CI:1.35,2.87) and obesity (OR:2.1, 95% CI: 1.5,2.8), moderate alcohol use (OR: 0.7, 95% CI:0.5,0.9), moderate (OR 0.7, 95% CI: 0.55,0.98) or high (OR 0.6, 95% CI: 0.4,0.8) physical activity level, and healthy diet (OR 0.8, 95% CI: 0.75,0.95, per 10 points) were associated with substantial pain. Conclusions: Our results show clear associations with modifiable lifestyle factors and substantial pain in MS. These factors are already considered in the prevention and management of pain in other populations but have not previously been considered in MS. Conversely, pain, and associated common MS comorbidities such as depression, anxiety and fatigue may hamper efforts to start or maintain healthy behaviours. Strategies to overcome these barriers need to be considered. Further research should clarify the direction of these associations.